The Bovine Pangenome Consortium: Democratizing production and accessibility of genome assemblies for global cattle breeds and other bovine species - Smith, T.P.L.; Bickhart, D.M.; Boichard, D.; Chamberlain, A.J.; Djikeng, Appolinaire; Yu Jiang; Wai Y. Low; Pausch, H.; Demyda Peyrás, S.; Prendergast, J.; Schnabel, R.D.; Rosen, B.D.; et al. (Springer, 2023)
The Bovine Pangenome Consortium (BPC) is an international collaboration dedicated to the assembly of cattle genomes to develop a more complete representation of cattle genomic diversity. The goal of the BPC is to provide genome assemblies and a community-agreed pangenome representation to replace breed-specific reference assemblies for cattle genomics. The BPC invites partners sharing our vision to participate in the production of these assemblies and the development of a common, community-approved, pangenome reference as a public resource for the research community (https://bovinepangenome.github.io/). This community-driven resource will provide the context for comparison between studies and the future foundation for cattle genomic selection.